PENGARUH MEDIA EDUCAPLAY BERBASIS QUIZ PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS III SD NEGERI 69 BANDA ACEH - Nadia Sofana; Teuku Mahmud; Regina Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of Quiz-based Educaplay media in Indonesian Language subjects to increase the learning interest of Grade III students at SD Negeri 69 Banda Aceh, specifically regarding Heroic Stories material. Educaplay learning media based on Quizzes aims to enhance student learning interest through fun, technology-based interaction. This study utilized a quantitative approach with a pre-experimental design using the one-group pretest-posttest method, involving 30 students without a control group. Data were collected through test instruments (pretest-posttest) and observation sheets. The collected data were analyzed using statistical tests (t-test). The normality test results using Shapiro-Wilk showed a pretest score of 0.53 and a posttest score of 0.73. The hypothesis testing results using the paired sample t-test yielded a value of 0.00 (≤ 0.05), with an average increase of 24.333. This indicates that the use of Quiz-based Educaplay media has a positive influence on increasing students' learning interest in Indonesian Language subjects. The conclusion of this study is that Quiz-based Educaplay media in Indonesian Language subjects is effective in increasing students' learning interest in Heroic Stories material.